In vitro Hemostasis Activity Analysis of Ethanol Extract of Sappan Wood Administration Based on Clotting Time Lee and White Method - Saptaningtyas, Ragil; Putri Sulfitri; Annisa Nurul Hikmah; Erma Lestari; Joko Teguh Isworo; Mohd Hanif Zulfakar (Window of Health : Jurnal Kesehatan, 2024)
Hemostasis is a combination of events following vascular injury, including vasoconstriction, platelet aggregation, thrombus formation, recanalization, and debridement. Clotting time is an assessment to determine the time required for blood to clot in vitro. This study aimed to determine the effect of sappan wood ethanol extract on the outcome of the clotting time test using the Lee and White method. This study is experimental, with several samples of 32 divided into three groups, using the Lee and White method clotting time examination. Group C as a control group (1 mL of venous blood only), P1 and P2 as much as 1 mL of venous blood by adding 0.3 grams and 0.4 grams of sappan wood ethanol extract, respectively. The data analysis used was One-way ANOVA with Post hoc LSD test. One-way ANOVA test revealed significant differences between research groups (<0.05). Post hoc LSD results showed a significant difference between P1 and P2 compared to group C. It can be summarized that there is a difference in the results of the Lee and White method clotting time examination between blood with and without sappan wood ethanol extract.